RONGGENG KALER’S ART PURBASARI JAYA’S GROUP - Senja, Adam (Penerbit Lafadz Jaya, 2022)
The purpose of this article is to find out the structure of the show, and the music of ronggeng kaler’s show that has been formed to this article by the title “Ronggeng Kaler Purbasai Jaya’s Group In a Wedding Events“. The method in this research is descriptive analysis by qualitative approach. Ronggeng Kaler‘s art is a traditional art from Ciamis and Pangandaran. Called Ronggeng Kaler it caused by the development this art is in the north area. In sundanesse it called kaler. Ronggeng Kaler’s art is a development by Ronggeng Gunung’s art which is the performance is not only the music but there are also a dance unsure. Music instrument that used in this art is a set of salendro’s gamelan. Ronggeng Kaler’s art is usualy for entertainment show but in another occasion also for special ceremonial. Hopefuly, this article can be advantages for a lot of people especialy for teachers, artist, arts observer and others.